2015
DOI: 10.1111/cas.12800
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ADAM10 upregulation on progression, migration, and prognosis of nasopharyngeal carcinoma

Abstract: A disintegrin and metalloprotease 10 (ADAM10) is a typical member of the ADAMs family, which has been reported to be upregulated in various types of cancers and contribute to cancer progression and metastasis. However, little is known about the role of ADAM10 in nasopharyngeal carcinoma (NPC). The purpose of this study is to explore ADAM10 expression status and its biological functions in NPC. We first examined the expression of ADAM10 in NPC tissues and cell lines by immunohistochemistry, Western blotting, PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 34 publications
(96 reference statements)
3
38
1
Order By: Relevance
“…For NPC tissues, the staining intensity was categorized as strong (2), weak (1), or negative (0) semiquantitatively using the following scale: 0, 0% of cells; 1, 1e25% of cells; 2, 26e50% of cells; 3, 51e75% of cells; and 4, 76e100% of cells. The scoring results of intensity and extent were multiplied as described previously [19]. The samples with a final score <4 were regarded as CD93 negative or weak expression and 4e8 were determined as over-expression.…”
Section: Immunohistochemistry (Ihc) and Western Blot Analysismentioning
confidence: 99%
“…For NPC tissues, the staining intensity was categorized as strong (2), weak (1), or negative (0) semiquantitatively using the following scale: 0, 0% of cells; 1, 1e25% of cells; 2, 26e50% of cells; 3, 51e75% of cells; and 4, 76e100% of cells. The scoring results of intensity and extent were multiplied as described previously [19]. The samples with a final score <4 were regarded as CD93 negative or weak expression and 4e8 were determined as over-expression.…”
Section: Immunohistochemistry (Ihc) and Western Blot Analysismentioning
confidence: 99%
“…High expression of one or both of these closely related metzincin metalloproteinases portends unfavorable outcomes in biliary, breast, cervical, gastric, hepatocellular, lung, nasopharyngeal, ovarian, pancreatic, skin, and urothelial malignancies. [1][2][3][4][5] They also predict treatment resistance in breast, colorectal, hepatocellular, and lung cancers. [6][7][8][9] Long-standing dogma held that metalloproteases contribute to tumor growth and metastasis through enzymatic degradation of the extracellular matrix and tumor cell attachments.…”
Section: Introductionmentioning
confidence: 99%
“…β-catenin could dissociatd from the cytoplasmic tail of E-cadherin and its translocation into the nucleus to regulate the expression of certain genes [31]. In addition, thorsten et al [12] found that ADAM10 mediated E-cadherin shedding and regualted β-catenin translocation. In aother study, ADAM10 decreased E-cadherin protein level and inhibited β-catenin pathway in hepatocellular carcinoma [32].…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies revealed that the expression of ADAM10 was overexpressed in a variety of tumors including liver cancer [5], melanoma [6], gastric cancer [7], lung cancer [8], pancreatic cancer [9], and bladder cancer [10]. In addition, the silencing of ADAM10 inhibited significantly cell growth and metastasis [11][12][13]. Thorsten Maretzky et al [14] found that the shedding of E-cadherin caused by ADAM10 regulated the β-catenin subcellular localization and its downstream genes.…”
Section: Introductionmentioning
confidence: 99%